Circumpolar Landcover Units ... - Bartsch, Annett; Efimova, Aleksandra; Widhalm, Barbara; Muri, Xaver; von Baeckmann, Clemens; Bergstedt, Helena; Ermokhina, Ksenia; Hugelius, Gustaf; Heim, Birgit; Leibmann, Marina (Zenodo, 2023)
Landcover units have been derived from Copernicus Sentinel-1 und Sentinel-2 data acquired between 2016 and 2022 for the Arctic tundra biome. 23 units of which 20 represent different vegetation characteristics and soil conditions are provided. The units have been identified with K-means over a representative transect and in a second step retrieved across the entire Arctic north of the treeline. The description of the units is based on several thousand samples from vegetation surveys and soil probes. The units are supplied at 10m resolution in nine irregular tiles. Auxiliary data for quality information and input acquisition dates are supplied in a separate shape file. Classes are documented in detail in Bartsch, A., Efimova, A., Widhalm, B., Muri, X., von Baeckmann, C., Bergstedt, H., Ermokhina, K., Hugelius, G., Heim, B., and Leibmann, M.: Circumarctic landcover diversity considering wetness gradients, EGUsphere [preprint], https://doi.org/10.5194/egusphere-2023-2295, 2023. ... : Contains modified Copernicus Sentinel data 2016 - 2022. This study and associated datasets were designed for scientific purposes only and should not be taken as professional engineering advice. This work was supported by the European Space Agency CCI+ Permafrost and AMPAC-Net projects, the European Research Council project No. 951288, and has received funding under the European Union's Horizon 2020 Research and Innovation Programme under Grant Agreement No. 869471 (CHARTER). ...